Bandit queen - Khan, Nusrat Fateh Ali 1948-1997; White, Roger (Koch Vision, 2004)
The movie tells the story of the bandit queen Phoolan Devi who was sent to prison in 1983 and got free in 1994. During five years she was prosecuted by the Indian police and turned into a legend (like a modern Robin Hood) by the Indian press. Although the press tended to make her the optimal hero with blue eyes, dark hair, being tall and beautiful she was in reality an average Indian which makes it hard for the movie to fulfill the expectations of the audience and tell the truth at the same time. Later in her life,She entered into the politics and was assassinated in 2001. [Movie database]
Bildformat 4:3
Orig.: Großbritannien, Indien 1994